(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The aim of the article is to show the national - cultural seam of affection in the meaning of the words in the English and Uzbek languages. Scientific research in the fields of cognitive linguistics, language and culture, language and society, linguoculturology, pragmatics, sociolinguistics, ethnolinguistics, which are developing today, requires a comprehensive analysis of words, phrases and phraseological units.